(untitled) (Ustozlar uchun, 2025)
This research explores how transformational leadership accelerates innovation processes within project-based organizations, using Uzbekistan as a case context. Through a mediation-based model, the study identifies psychological safety, innovation climate, and knowledge sharing as key mechanisms linking leadership to innovation speed and effectiveness. The example of IT Park Uzbekistan demonstrates how these mechanisms are emerging in practice through startup support, cross-functional teamwork, and a “fail fast, learn fast” culture. The findings suggest that transformational leadership should be understood as a catalyst that creates the social and psychological conditions necessary for innovation. The study concludes that integrating leadership development with national innovation policy may strengthen Uzbekistan’s transition toward a modern, knowledge-driven economy.